Evaluation of breeding values of Hariana bulls under organized farms - SINGH, UMESH; KUMAR, ARUN; BENIWAL, B K; KHANNA, A S (The Indian Journal of Animal Sciences, 2011)
Best linear unbiased prediction (BLUP) procedure was used to evaluate the breeding value of 33 Hariana bulls (used in 4 sets) on the basis oftheir daughters frrst lactation milk yield, maintained at Germplasm unit, CCS HaryanaAgriculture University, Hisar, Government Livestock Farm (GLF), Hisar; Kurukshetra Gaushala, Hisar, Bhiwani Gaushala and lind Gaushala and calved during 1992 to 2005 were utilized for present study. The breeding values of bulls of different sets varied from 840.82 to 901.75 kg in fIrst set, from 827.56 to 891.60 kg in second set, from 876.68 to 927.56 kg in third set and from 834.05 to 880.53 kg in fourth set. The highest breeding value was observed for sire numbers 67-A (927.56 kg) followed by 45-A (923.21 kg) and 47-A (921.10 kg) of third set and their superiority over the herd average ranged between 46.52 and 52.98 kg (5.31 to 6.05%). It indicated genetic progress over different sets of bulls, as bulls of third set were superior to first and second sets. However, perfonnance of fourth set bulls slightly declined Â